The Impact of Lecture and Interactive Methods onStudent’s English Competency - Muhammad Suhaimi taat; Abdulbaki, K.; Al-Saqqaf, A. (Kassel University Press GmbH, 2020)
The current research deals with the perceptions of non-native students at a university college in Oman on the use of the lecture and interactive methods in teaching English. The aim is to find out the method which may assist satisfactorily in improving students’ English language competency in terms of skills, developing their cognitive abilities and enhancing their personal growth. This study employs the quantitative approach through conducting and analyzing students’ questionnaires related to the lecture and interactive methods of teaching. The findings of this research indicate that the interactive methods are highly viewed by students while the lecture is lower. However, weak students incline to the lecture method in contrast to average, good and very good students. The implications of the use of both methods could be extended to the social side of education. Students exchange ideas, suggestions and feelings which contribute to strengthening their relationships as colleagues. They would practice expressing their thoughts freely and respecting the viewpoints of others no matter whether they agree or disagree with them. Consequently, this would have positive impacts on their lifestyle when dealing with their surrounding society and in workplaces in later stages.